Place identity and destination image of Davao City and its influence on place attachment designing for a tourism development in Davao City - Colon, Lou Kimberly L. (2019)
Tourism is a center of economic, opportunity and innovation. The study examined the potential of the tourist?s perception of destination image to help identify significant attributes or characteristics of a tourism destination setting and identify the factors that influence tourist place attachment. It also captured the identity of the city through the perception of its citizens to establish a branding that will contribute to the identity of the city as a whole. The research utilized the theory of Destination Image which is basically the physical, emotional and the experiential memory of a person on a particular destination and is the affective link between person and space. Along with Place Identity, which intends to highlight the creation of a place with the importance of reflecting the identity of the place from the perception of the locals, was also used in creating the framework of this study. The study used a quantitative method in gathering data but used qualitative method in synthesizing the results and the interpretation of the data. The data was collected and obtained thru self-administered structured survey questionnaires. The survey questionnaire consists of three parts: Destination Image Measurement, Place Identity and Place Attachment assessment. It can be inferred that social imageability is the strongest key player in the construction of place identity in Davao City. Basically, social image ability is identified through civic engagement, parades, celebrations and religious life. The examination of destination image, place identity and place attachment to be explored as potential predictors and resources with regard to the creation of place, should be incorporated in the design of the tourism development that seeks to strengthen the connection between people and the place as well as maintain competitiveness in the tourism market and build a strong tourism branding and identity of the city.